The determination of stability constants of N-salicylidene anilines, metal complexes by potentiometric method - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2004)
The stability constants of the complexes which were formed from N-salicylidene-aniline (HBDA), N-salicylidene-4-bromoaniline (HBDBrA), N-salicylidene-4-chloroaniline (HBDCA) with chromium(III), manganese(H). cobalt(II), nickel(II), copper(II), zinc(II) and cadmium(II) were determined potentiometrically by using Calvin-Bjerrum and Irwing-Rossotti methods in this work. The protonation constants and dissociation constants of the ligands were found at 25degreesC and for I = 0.11 are given below; HBDA logK(1) = pK(2) = 9.15; logK(2) = pK(1) = 4.75 HBDCA logK(1) = pK(2) = 9.00; logK(2) = pK(1) = 4.00 HBDBrA logK(1) = pK(2) = 8.40; logK(2) = pK(1) = 3.65 The formation constants of complexes formed with Cr(III). Mn(II). Co(II), Ni(II), Cu(II),Zn(II),Cd(II) are in the order: 14.40; 3.40; 4.30; 4.36; 11.90; 4.70; 3.71 for HBDA; 10.96; 4.16; 4.09; 4.56; 11.56; 4.49; 3.80 for HBDCA; 13.64; 3.55; 3.99; 4.55; 11.71; 4.24; 3.55 for HBDBrA. The conditional formation constants and the formation pH ranges of complexes were determined. Relative abundance was plotted using conditional formation constants of the complexes and the steps of the formation of the complexes were shown in graphs. The composition of chromium and copper complexes for bidentate ligands were determined as metal/ligand = 1:2 while other metal complexes were metal/ligand = 1:1.
Keywords: stability constants; potentiometric titration; metal complexes; N-salicylideneaniline; METABOLISM